2017
DOI: 10.24896/jmbr.2017744
|View full text |Cite
|
Sign up to set email alerts
|

Production of biopolyester poly(3-hydroxybutyrate) by Bacillus cereus RCL 02, a leaf endophyte of Ricinus communis L.

Abstract: Endophytic bacteria colonizing the internal tissues of plants have attracted the attention of scientific communities in recent years for production of biodegradable polyesters like polyhydroxyalkanotaes (PHAs). A newly characterized bacterium, Bacillus cereus RCL 02 (GenBank accession no. KX458035), isolated from surface sterilized leaves of Ricinus communis L. has been explored for the production of poly(3-hydroxybutyrate) [P(3HB)], the most common PHA. As revealed by scanning electron microscopy, P(3HB) accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…These reports focussed primarily on the process optimization for PHA production using sugarcane molasses with very little emphasis on the material properties of the accumulated biopolyesters. in mineral salts medium containing glucose as the sole source of carbon [13]. The present study demonstrates the bioprocessing as well as partial characterization of P(3HB-co-3HV) copolyesters produced by the endophytic isolate RCL 02 following bioconversion of sugarcane molasses as the sole source of carbon in the growth medium.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…These reports focussed primarily on the process optimization for PHA production using sugarcane molasses with very little emphasis on the material properties of the accumulated biopolyesters. in mineral salts medium containing glucose as the sole source of carbon [13]. The present study demonstrates the bioprocessing as well as partial characterization of P(3HB-co-3HV) copolyesters produced by the endophytic isolate RCL 02 following bioconversion of sugarcane molasses as the sole source of carbon in the growth medium.…”
Section: Introductionmentioning
confidence: 62%
“…glucose, sucrose, maltose etc. [13]. It may also be presumed that molasses served not only as a potential source of carbon but also provided vitamins and other essential growth factors for effective growth and sustainable production of the biopolyester by the isolate RCL 02.…”
Section: Growth Kinetics and Accumulation Of Phamentioning
confidence: 99%
“…This study revealed a 2.81-fold enhancement (2.87 to 8.07g/L) of P(3HB) production by the endophytic B. cereus RCL 02 after optimization using response surface methodology in comparison to the preliminary OVAT studies. 11 Production of biopolyester (8.07g/L) by the leaf endogenous isolate B. cereus appeared to be quite satisfactory and compared well with other Bacillus spp. so far reported.…”
Section: Validation and Confirmation Of The Modelmentioning
confidence: 84%
“…Selection of the fermentation variables and their lower and higher levels were decided based upon the results obtained from 'OVAT' experiments. 11 Growth (Y 1 ) and P(3HB) production (Y 2 ) were executed in a set of 12 experiments following the PB design. The significance level (p value) of each variable was determined using Fisher's F-test.…”
Section: Experimental Design and Optimization Using Wrsmmentioning
confidence: 99%
“…However, B. megaterium showed maximum PHB accumulation when glucose was used as carbon source (Hori et al, 2002). Bacillus species has been reported to accumulate PHB up to 90% of cell dry weight by utilizing soy molasses oligosaccharides like raffinose without the need for nutrient limitation (Full et al, 2006;Das et al, 2017).…”
Section: Production Of Phbmentioning
confidence: 99%